Paediatric Anti‐Müllerian Hormone measurement: Male and female reference intervals established using the automated Beckman Coulter Access AMH assay. Issue 4 (18th July 2018) - Jopling, Helen; Yates, Allen; Burgoyne, Nicholas; Hayden, Katharine; Chaloner, Christopher; Tetlow, Lesley
Summary: Objective: Anti‐Müllerian Hormone (AMH) concentration is high at birth in males, demonstrating the presence of functional testicular tissue in the prepubertal period, and acting as a useful marker in the investigation of paediatric reproductive disorders. AMH also provides a tool in the investigation of female virilization, premature ovarian failure and polycystic ovarian syndrome in childhood. Robust, assay‐specific paediatric AMH reference intervals are therefore required for clinical interpretation of results. The aim of this study was to derive age‐specific AMH reference intervals for males and females aged 0‐18 years. Design and Patients: Plasma samples were obtained from patients at Royal Manchester Children's Hospital and analysed for AMH using the automated Beckman Coulter Access AMH Assay. Patients under investigation for paediatric reproductive or endocrine disorders were excluded from the study. Measurements: Seven hundred and 2 patient plasma samples (465 male, 237 female) were subject to AMH measurement, and results were analysed in order to derive continuous and discrete reference intervals for the paediatric age range. Results: Clear discrimination between male and female AMH results was evident in the prepubertal age range, with some overlap between the genders following pubertal onset. Conclusions: We have derived age‐related reference intervals for plasma AMH in the paediatric age range (0‐18 years) using the automated Beckman Coulter Access AMH assay which will aid in the investigation of paediatric endocrine disorders such as disorders of sexual development. Abstract : A study to establish age‐related reference intervals for Anti‐Müllerian Hormone (AMH) from birth to adulthood for males and females.